The teaching of aerospace vehicle design at Cranfield University with particular reference to the group design project - Stocking, P. J. (Professional Engineering Publishing, 2007)
Over the years, the aircraft design course at Cranfield has evolved into the postgraduatemaster's programme in aerospace vehicle design that we have today. One of the unique featuresof the course is the extensive group design project, which has played a fundamental part inaircraft design education right from 1948 up to the current day. The success of the course, andthe student experience, depends on the success of the group design project. The philosophy ofthe role of the group design project in the teaching of aircraft design is discussed in detail in thispaper. Examples are presented of recent subject aircraft along with some novel features ofthese designs.